(untitled) (International Journal of Engineering and Computer Science, 2021)
This study aims to determine how much electric power can be generated from methane gas obtained from organic waste and how much electrical energy has not been utilized from the potential methane gas produced and how much volume of pyrolysis oil is produced from plastic waste produced by the people of the City. Kendari. To obtain the electrical energy produced, the volume of waste is first calculated so that the potential for waste (Q), Biogas Production Volume (VBS), and Methane Gas Volume (VGM) can be obtained. Referring to Kadir’s research, 2012, the volume of pyrolysis oil produced by Kendari City is obtained. The results showed that the energy produced from the Puuwatu TPA in a daily average was 288,466,5332 kWh. While the energy flowing through the Mandirin Energi area is 125 houses and each house with a power of 450 VA (MCB 2 Ampere), the daily count used to fulfill the energy independent area is 1,080 kWh, so that energy has not been utilized from its potential. in Puuwatu TPA is 287,386.5332 kWh. While the production of plastic waste in Kendari City per year is 792 tons, the average plastic waste produced in 500 grams is 423.25 ml of pyrolysis oil or the equivalent of 1000 grams produces pyrolysis oil of 845.6 milliliters, so the amount of plastic waste in Kendari City per year year it can produce pyrolysis oil of 670 428 000 liters. Keywords: Organic Waste, Methane Gas, Electrical Energy, Pyrolysis Oil, Plastric Waste.